Contamination of typical phthalate acid esters in surface water and sediment of the Pearl River, South China: Occurrence, distribution, and health risk assessment - Huike, Zhang; Chao, Zhang; Yifeng, Huang; Xiaohui, Yi; Xujun, Liang; Lee, Chang Gu; Mingzhi, Huang; Guang-Guo, Ying (Journal of Environmental Science and Health - Part A Toxic/Hazardous Substances and Environmental Engineering, 2022)
The occurrence and distribution of six phthalate acid esters (PAEs) in surface water and sediment of the Pearl River were investigated, including Xijiang River (XR), Beijiang River (BR), Lingdingyang Estuary (LE), and Guangzhou River (GR) in South China. Six target PAEs were identified in surface water and sediment at almost all sites in the Pearl River, with di(2-ethyl-ethyl) phthalate (DEHP) and dibutyl phthalate (DBP) as dominant PAEs. Total 6 PAEs (ΣPAEs) in surface water and sediment ranged from 1,797.5 to 4,968.5 ng L−1 and 95.24 to 3,677.26 ng g−1 dw, respectively. In addition, the contamination levels of PAEs in the Pearl River are in the following order: XR > BR > GR > LE for surface water and BR > XR > GR for sediment. Local agricultural activities, industrial production, water confluence, and seawater intrusion are the probable sources of PAEs in the Pearl River. Based on correlation analysis, the possible collocation patterns of different PAEs were revealed. The risk assessment indicates that residual PAEs in the Pearl River pose a serious threat to the ecological environment. According to risk characterization of fish living in the Pearl River, the decreasing order of health risks was: GR > LE > XR > BR.
Keywords: Acid ester; Beijiang rivers; Contamination levels; Distribution characteristics; Guangzhou; Health risk assessments; Occurrence and distribution; Phthalates; South China; Spatial distribution characteristic; Animals; China; Dibutyl Phthalate; Esters; Phthalic Acids; Risk Assessment; Rivers; Water; Water Pollutants, Chemical; contamination levels; sediment; spatial distribution characteristics; Surface water